Understanding Down Syndrome: Global Perspectives, Advances, and Challenges in the Context of Bangladesh - Ahmed, Rashed; Tamim, Md. Tanzimur Rahman (Balai Publikasi Indonesia, 2025)
Down syndrome (DS), or Trisomy 21, is a genetic disorder characterized by intellectual disabilities, developmental delays, and various health complications. This comprehensive review examines the causes, symptoms, and management strategies of DS, emphasizing global research advancements and their relevance to Bangladesh. This article highlights emerging therapies, genetic studies, and social advocacy efforts, proposing strategies to bridge the gap in healthcare and research. It aims to inspire collaborative efforts to improve the quality of life for individuals with DS globally and within Bangladesh. Down Syndrome (DS), or Trisomy 21, is a genetic disorder characterized by developmental delays, intellectual disabilities, and a variety of health complications. This review explores the causes, symptoms, and management strategies of DS, emphasizing the latest global advancements such as CRISPR gene editing and neurodevelopmental imaging. Despite these breakthroughs, Bangladesh continues to face significant challenges in diagnosing and managing DS due to inadequate healthcare infrastructure, limited diagnostic resources, and persistent societal stigma.The paper highlights disparities in outcomes for individuals with DS between developed and developing nations, focusing on the stark differences in healthcare access, early intervention programs, and societal acceptance. Case studies illustrate the successes of advanced therapies in developed countries while underscoring the gaps in resources and awareness in Bangladesh. These findings emphasize the urgent need for targeted interventions, including improved diagnostic tools, enhanced healthcare systems, and inclusive social practices in developing nations.Additionally, the article examines the role of emerging therapies and advocacy efforts in bridging these gaps. By leveraging global advancements, promoting public-private partnerships, and fostering international collaborations, the study proposes actionable strategies to improve the quality of life for individuals with DS.